PEMANFAATAN TEPUNG BIJI DURIAN UNTUK PENGEMBANGAN TERNAK PUYUH - Wismalinda Rita; Neli Definiati; Lezita Malianti (SINAR SANG SURYA, 2019)
Quail (Coturnix-coturnix japonica) including poultry that has the potential to be developed but in increasing production is still constrained by the problem of seeds, feed, and post-harvest processing. Not yet utilized durian seeds as a source of local feed ingredients which is very potential for quail cattle. Besides the low understanding of partners about the nutritional needs of quails and post-harvest processing. This Community Service Program (Program Pengabdian Masyarakat/PKM) aims to overcome the problems of seed and quail seed quality obtained, utilizing durian seed waste for quail feed and post-harvest processing of male quail. The activity has been carried out for 8 (eight) months from March to October 2018 in the “Usaha Ternak Maju Group” and the “Kasih Ibu” Orphanage group in the form of socialization, counseling, training, and demonstrations as well as making a demonstration plot. PKM activities have been going well with the two partners shown by the use of durian seed-based feed ingredients to increase quail livestock production. Both partners have understood hatchery management, quail maintenance management, durian seed flour making technology and management of ration preparation using durian seed flour and male quail processing.